Comparison of effectiveness of laparoscopic and transvaginal mesh operations in uterus protective surgery of women in reproductive-age with pelvic organ prolapse (stage ≥2). - Ünal Turkay; Gökmen Sukgen; Mehmet Ozsurmeli (Cukurova Medical Journal, 2021)
Purpose: The aim of this study was to compare the efficiency of laparoscopic and transvaginal mesh operations with conservative surgery of reproductive-age women with pelvic organ prolapse (stage≥2) (POP). Materials and Methods: In this study, we retrospectively evaluated 22 cases of 105 patients who diagnosed with symptomatic POP-Q stage 2 and above pelvic prolapse, part of whom underwent laparoscopic surgery (Group-1) while the other part composed of those who underwent transvaginal mesh (TVM) surgery (Group-2). Urogenital prolapse Pelvic Organ was graded using POP-Q.As the current TVM surgical kits four-arms mesh was used. Results: The mean age of the patients of both groups was 42.2±11.4 and 38.3±12.8 years, respectively. The mean duration of hospitalization for the patients underwent laparoscopy was 2.3 days (range:1-4 days), that period was observed as 3 days in Group-2 (range:2-4 days). None of our patients had any adverse reactions in the early or late stages. The rate of success was 95.45% for patients who underwent laparoscopic surgery, while it was 98.10% for the group of TVM surgery. Conclusion: Transvaginal mesh surgery was found to be a relatively successful technique in pelvic organ prolapse surgery owing to the high rate of success and minimal rates of complications.